(untitled) (Research, Society and Development, 2022)
The number of obese or overweight people in contemporary society increases every year. Obesity is an epidemic that accompanies other comorbidities that are components of the obese syndrome, such as type II diabetes, hypertension, dyslipidemias, increased visceral adipose tissue, increased risk of heart disease, and cancer, in addition to other problems arising from obesity, such as: injuries, lack of motivation, lack of dietary control, and irregularity in an exercise program. There is evidence that reinforces the benefits of physical activity for weight loss and weight control, as well as for improving the individual’s quality of life. However, there is no consensus about the most effective methodology for weight loss. The objective of this review was to analyze the effectiveness of different types of training for weight loss based on what the literature has available today. For this research, we used the Scielo databases and the Scholar Google search site. The results showed that there is still much to be clarified in the area of exercise prescription for weight loss, showing that there is no ideal methodology, but there is one that suits the specific student, following the principles of training, biological individuality, and the wishes of this student.